Antispasmodic Efficacy of Ethanolic Extract of Chamomile Flowers in Isolated Chicken Ileum Using Ex-Vivo Experiments - Vaibhav Dwivedi; Nisha Gautam; Priya; Avinash C. Tripathi (Asian Journal of Pharmaceutical Research and Development, 2025)
Matricariachamomilla L. (Chamomile), a member of the Asteraceae family, has long been valued in traditional medicine for its broad therapeutic applications, including the relief of smooth muscle spasms. Its pharmacological properties are attributed to a diverse range of bioactive constituents present in its essential oils and plant extracts. Ethanolic extracts were prepared from disc florets, ray florets, and their combination. Phytochemical screening was conducted to identify major classes of constituents. The effect of the extracts on acetylcholine-induced contractions was assessed using the interpolation method, and responses were recorded with a kymograph. Dose response relationships for acetylcholine were determined in the absence as well as presence of the extracts. Phytochemical analysis revealed the presence of alkaloids, flavonoids, phenolic compounds, tannins, and triterpenoids, with varying intensity across flower parts. Pharmacological assays demonstrated that ethanolic extracts significantly reduced acetylcholine-induced ileum contractions in at higher dose, indicating antagonistic activity. The combined extract of ray and disc florets showed the greatest inhibitory effect. The findings support the traditional use of M. chamomilla L. as an antispasmodic agent. The inhibitory effect on acetylcholine-induced smooth muscle contraction suggests possible interference with parasympathetic neurotransmission. Further studies may need to identify the specific active compounds and elucidate their exact mechanisms of action.